Occurrence, spatial distribution, and risk assessment of brominated flame retardants in farmland soils of typical provinces in China. (February 2023) - Tholley, Mabinty Sarah; George, Lartey Young; Fu, Mengru; Qiao, Zhihua; Wang, Gehui; Ling, Siyuan; Peng, Cheng; Zhang, Wei; Ye, Chunmei; Liu, Fang; Yang, Jie
Abstract: In the present study, we investigated the occurrence, distribution, and potential risks of 4 brominated flame retardants in farmland soils across 18 provinces of China. The total mean concentrations of the BFRs were in order as DBDPE > BDE209 > HBB > TBB. DBDPE concentration was highest at 177.208 ng/kg, revealing its long-term use and persistence across the study areas. In parts of China, DBDPE was highest in the south (Sichuan, Shaanxi and Guangdong provinces), BDE209 was highest in the south (Sichuan province) and north (Jilin province), while HBB was highest in the south (Sichuan province) and east (Anhui and Zhejiang provinces) of China. Comparisons of the results in this study to other reported studies in different regions indicated that the studied BFRs concentrations were higher in the studied provinces of China. Pearson correlation between BFRs revealed both positive and negative associations within the BFRs groups and between BFRs and soil properties (SOM, CEC, pH, EC and PS%). The mean hazard quotients (HQ) of ecological risks ranged from 8.76 × 10 −6 to 1.16 × 10 −2 (HQ < 1) while non-carcinogenic human health risk evaluation for adults ranged from 7.05 × 10 −7 - 7.48 × 10 −4 (HQ < 1) and for children 2.99 × 10 −4 - 4.30 × 10 −2 (HQ < 1). Although the risk evaluations of BFRs from farmland soils in this study were low, the results serve as useful indicators of potential cumulative and long-term threats of BFR to rural areas where there is a high conversion of agricultural lands to non-agricultural use. Graphical abstract: Image 1 Highlights: BFRs concentrations from the typical farmland soils in China were evaluated. BFRs distribution was the highest in the south and east parts of 18 provinces studied. Dermal absorption and oral ingestion were main plausible exposure route for both children and adults.